INTEGRATION OF MOTOR-ASSISTED PLANETARY CVT SYSTEMS FOR WIND TURBINES UNDER VARIABLE WIND CONDITIONS (KIUT Publication, 2025)
This paper presents a novel continuously variable transmission (CVT) system for wind turbine applications, combining a planetary gearbox with a motor-assisted control mechanism. The proposed architecture enables real-time adjustment of the transmission ratio by dynamically regulating the ring gear using a synchronous electric motor. A detailed mathematical model is developed to describe the gear kinematics and torque distribution, followed by a complete Simulink implementation that captures the electromechanical interactions between the turbine input, planetary gear system, and motor controller